Aplikasi Asam Humat dan Pupuk Organik Cair Ekstrak Rumput Laut untuk Meningkatkan Pertumbuhan dan Kandungan Flavonoid Brassica juncea L. - Tia Setiawati; Sania Septiani Fitria; Mohamad Nurzaman; Rusdi Hasan; Asep Zainal Mutaqin; Ani Lestari (Pro-Life, 2024)
This research was conducted with the aim of obtaining the optimal dose of humic acid (HA) and liquid organic fertilizer (LOF) from seaweed extract that can enhance the growth and total flavonoid content of Brassica juncea L. The method used in this study was experimental with a randomized complete block design with two factors. The first factor was HA, consisting of 4 dose levels: 0, 4, 8, and 12 g/kg, while the second factor was LOF from seaweed extract, consisting of 4 dose levels: 0, 1, 2, and 3 mL/L. Each treatment was replicated four times. Parameters were observed on the 42nd day, including plant height, leaf number, leaf area, dry weight, and total flavonoids. Data were analyzed using Analysis of Variance (ANOVA) and followed by Duncan's Multiple Range Test with a confidence level of 95%. The results showed that the dose of 4 g/kg HA and 2 mL/L LOF was the best dose for enhancing growth and total flavonoid content, producing an average plant height of 19.25 cm, a leaf number of 5.75, a total leaf area of 179.8 cm2, a dry weight of 0.57 grams, and a total flavonoid content of 0.106 mg QE/g sample.